2017
DOI: 10.1016/j.ypmed.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between drugs affecting the renin-angiotensin system and colorectal cancer: The MCC-Spain study

Abstract: The potential protective effect of Renin-angiotensin system (RAS) inhibitors is a subject of increasing interest due to their possible role as chemopreventive agents against colorectal cancer (CRC). To evaluate this association, we conducted a case-control study with 2,165 cases of colorectal cancer, diagnosed between 2007 and 2012, and 3,912 population controls frequency matched (by age, sex and region) from the Spanish multicenter case-control study MCC-Spain. We found a significant protective effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Increased AGTR1 gene expression is associated with breast cancer [ 85 ], and ARBs inhibit mammary tumor formation in mice [ 86 , 87 ]. Similar, to the observation of no increase in AT1R gene expression in this study, ARB usage did not have a protective effect against CRC in a retrospective study of a large Spanish population [ 96 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Increased AGTR1 gene expression is associated with breast cancer [ 85 ], and ARBs inhibit mammary tumor formation in mice [ 86 , 87 ]. Similar, to the observation of no increase in AT1R gene expression in this study, ARB usage did not have a protective effect against CRC in a retrospective study of a large Spanish population [ 96 ].…”
Section: Discussionsupporting
confidence: 88%
“…There is considerable variance in the reported effects of ACE inhibitors on cancer risk with some studies of CRC showing a chemoprotective effect [ 18 , 109 ]. Beneficial effects of ACE inhibitors on CRC were found to be greatest in men under 65 years of age [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 931 related articles were obtained in the initial inspection, which were screened by layer and 16 were finally included, comprising 16 randomized controlled trials involving 2,847,597 participants. 9 24 The flow chart of the literature search is presented in Figure 1 . The characteristics of the included studies are shown in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in 2010, Sipahi et al 3 suggested that ARB increased the risk of developing cancer and, conversely, the results of Bangalore et al 4 reported in 2011 that they were unrelated. In recent studies on various cancers and antihypertensive drugs, it has been reported that angiotensin‐converting enzyme inhibitor (ACE‐I) and ARB are associated with a decrease in the incidence of colorectal cancer, 5 while for lung cancer, there have been reports that ACE‐I is associated with increased cancer incidence 6 . Moreover, for breast cancer, it has been reported that antihypertensive drugs (ARB, ACE‐I, Ca blocker, β‐blocker, diuretics) are either associated with an increase in cancer incidence 7,8 or are not related 9 .…”
Section: Introductionmentioning
confidence: 99%
“…that angiotensin-converting enzyme inhibitor (ACE-I) and ARB are associated with a decrease in the incidence of colorectal cancer, 5 while for lung cancer, there have been reports that ACE-I is associated with increased cancer incidence. 6 Moreover, for breast cancer, it has been reported that antihypertensive drugs (ARB, ACE-I, Ca blocker, β-blocker, diuretics) are either associated with an increase in cancer incidence 7,8 or are not related.…”
mentioning
confidence: 99%